Case Report: Beckwith–Wiedemann syndrome with reduced H19 expression - Wang, Meng; Deng, Jiegang; Xing, Shuhua; Niu, Xuening (Frontiers in Pediatrics, 2025)
BackgroundBeckwith–Wiedemann syndrome (BWS) is a congenital imprinting disorder characterized by macrosomia, umbilical hernia, macroglossia, and increased tumor susceptibility. DNA methylation changes at 11p15.5 are its primary molecular mechanisms. This report presents a case of BWS wherein the patient registered a gain of methylation at imprinting control region 1 (IC1) and reduced H19 expression, along with typical clinical features and recurrent atrial tachycardia.Case presentationA 2-month-old female infant presented with macroglossia, umbilical hernia, organomegaly, and arrhythmia. She had a history of fetal macrosomia and polyhydramnios. Echocardiography revealed a patent ductus arteriosus, and an electrocardiogram confirmed atrial tachycardia. Multiplex ligation–dependent probe amplification testing showed normal copy number at 11p15.5 but a gain of methylation at IC1, confirming the diagnosis of BWS. When the patient was 12 months old, a tongue reduction surgery with ablation was performed because of feeding and speech difficulties experienced by the patient. A follow-up examination at 18–20 months showed no evidence of tumor development, improved pronunciation, and recurrence of atrial tachycardia without myocardial hypertrophy.ConclusionThis case underscores the diagnostic value of methylation testing in BWS, especially when the copy number is normal. Infants with macrosomia, macroglossia, and umbilical hernia should be evaluated for BWS. Long-term multidisciplinary follow-up, including tumor surveillance and cardiac monitoring, is essential for improving prognosis and quality of life.